Treatment of the Bitumen and Heavy Oil in Zubair Formation/ East Baghdad Field - Alhusseini, Dr. Ahmed K.; Mohammed, Harith A.; Hamzah, Sarah H. (Journal of Petroleum Research and Studies, 2024)
Bitumen precipitation refers to the separation and settling of heavier, denser hydrocarbon compounds from crude oil, which can occur under certain conditions of pressure and temperature. Crude oils with high viscosity, high density, low API gravity, and high sulfur content are more prone to bitumen precipitation. Understanding these properties is essential in the oil industry for predicting the behavior of crude oils during production, transportation, refining, and storage. The viscosity, density, API, and sulfur content of crude oil were examined as part of this investigation. The viscosity test is achieved by using automated viscometer apparatus with ASTM D 7042 standard, while the sulfur content test is performed by using Sindie 2622 Sulfur Analyzer with ASTM D 7039 standard. However, density and API gravity tests are done depending on manually condition related to mixing, time, method, temperature and percentages until obtained an optimized result. In order to determine the reduction in viscosity and other physical properties of crude oil, which will offer a better solution against the precipitating of asphaltene and Bitumen that essentially lead to plug the production pipe and stop oil production. The chosen solvent was kerosene, which mixed with three samples of crude oil over the course of three periods under standard conditions from the Zubair formation/East Baghdad field [EB-58]. However, the kerosene is selected because it has a high specific gravity which is considered as the best solvent for heavy crude oil and it is inexpensive. Moreover, in experimental work used three percentage of kerosene to mix with crude oil; [6%, 12% and 18%]. The results show that all ratio of kerosene addition will optimize the crude oil properties. The best result was gotten by adding 18 % kerosene to crude oil and the best optimization results were viscosity 89.3%, density 4.27%, API 39.5% and sulfur content 21.2%. In addition to reduce the viscosity of the heavy crude oil, using kerosene for 1 job will minimize the expenses approximately 1,177,000 IQD.